Integration of cultural, chemical and biocontrol methods in management of white root rot of apple - and J.N. SHARMA*, SHAKUN RANA, S.K. SHARMA (Indian Phytopathology, 2010)
Effect of integration of cultural, chemical and biocontrol methods was studied on the incidence of white root rot of apple caused by Dematophora necatrix to devise a suitable management strategy in nursery (2008). In pot culture (2007), all the combinations gave cent per cent disease control, and no disease incidence was recorded even after 60 days of inoculation. However, under nursery conditions, maximum disease control was recorded in a combination of deodar needles + neem cake + carbendazim (0.1%) + Trichoderma harzianum treatment. All the combinations were effective in improving plant health except the individual treatments in pot culture. In addition, all the treatments were at the same time effective in improving the plant health under nursery conditions.